A pilot evaluation of the online rabies exposure reporting system (R36) and post-exposure rabies immunization in clinical practice in selected hospitals in the upper north of Thailand in fiscal year 2016 - S, Arunothong; N, Bongjaporn; K, Thongchum (Biomedical Sciences and Clinical Medicine, 2020)
Objectives The study aimed to evaluate the online rabies exposure reporting system (R36) and rabies post-exposure prophylaxis (PEP) in clinical practice. Methods A cross-sectional pilot study was conducted in Wiang Kaen, Chiang Khong and Song Khwae Hospitals during mid-January 2017. Records for the 2016 fiscal year were reviewed and stakeholders were interviewed. Quantitative and qualitative attributes of the reports were evaluated. The administration of rabies PEP was also evaluated including the percentage rate of non-compliance with the Thai-CPG for rabies guidelines 2016 and pitfalls in actual practice. A few factors associated with the pitfalls were selected for analysis by multivariate logistic regression. Results Only the Wiang Kaen and Chiang Khong Hospitals used the online R36 reporting system. Ratings of the sensitivity, completeness and validity of the online R36 reports were 73.08%, 98.25% and 70.18%, respectively, for Wiang Kaen Hospital and 37.12%, 73.47% and 36.73% for Chiang Khong Hospital. The median time from the first dose to submission of the online report was 91 days in Wiang Kaen Hospital and 38 days in Chiang Khong Hospital. The rates of inappropriate PEP, i.e.under- or over-dosage of rabies vaccination/immunoglobulin injections, were 34.62%, 55.30% and 44.44% in the Wiangkaen, Chiang Khong and Song Khwae Hospitals, respectively. Factors associated with non-compliance with the guidelines occurred most frequently in 13-18 years old patients, head and neck injuries, laceration wounds and no history of previous adequate rabies vaccination. Conclusion The time to report in Wiang Kaen Hospital and the quality of the reports (sensitivity, completeness and validity) in Chiang Khong Hospital needed improvement. Overall, the incidence of inappropriate PEP was high for this fatal disease, indicating a need for physicians and health care teams to pay closer attention to patients who have the risk factors.